The Antiviral and Antitumor Effects of Defective Interfering Particles/Genomes and Their Mechanisms - Yang, Yicheng; Lyu, Taibiao; Zhou, Runing; He, Xiaoen; Ye, Kaiyan; Xie, Qian; Zhu, Li; Chen, Tingting; Shen, Chu; Wu, Qinghua; Zhang, Bao; Zhao, Wei (Frontiers in Microbiology, 2019)
Defective interfering particles (DIPs), derived naturally from viral particles, are unable to replicate on their own. Several studies indicate that DIPs exert antiviral effects via multiple mechanisms. DIPs are able to activate immune responses and suppress virus replication cycles, such as competing for viral replication products, impeding the packaging, release and invasion of viruses. Other studies show that DIPs can be used as a vaccine against viral infection. Moreover, DIPs/DI genomes display antitumor effects through inducing tumor cell apoptosis and promoting dentritic cells maturation . With genetic modified technique, it is possible to improve its safety against both virus and tumor. In this review, a comprehensive discussion on the effects exerted by DIPs is provided. We, further, highlight the clinical significance of DIPs and propose that DIPs can open up a new platform for antiviral and antitumor therapies.